Examining Teachers’ Roles in Early Childhood Sex Education: Insights from Indonesian Playgroups - Magta, Mutiara; Mustapa, Noviana; Pramitasari , Muktia; Risnawati , Erna; Kartikawati , Etty (JURNAL PENDIDIKAN USIA DINI, 2024)
This study investigates the roles of teachers in implementing sex education in Indonesian playgroups, focusing on their opinions, experiences, and methods. The research addresses the psychological effects of child sexual abuse and emphasizes the need for preventative measures through early education. Utilizing a qualitative approach, interviews were conducted with 13 teachers from various playgroups in Ciputat, Indonesia, and analyzed using Colaizzi’s method. The findings highlight two main themes: teachers' recognition of the importance of sex education and their practical experiences in implementing it. Most teachers agreed on the necessity of early sex education to promote awareness and protection against sexual violence. However, their understanding of the subject varied, with many expressing discomfort discussing sensitive topics. Teaching methods ranged from storytelling to demonstrations, but materials addressing reproductive organs were rarely included. The study underscores the importance of collaboration between teachers and parents to align educational goals. The findings contribute to the broader discourse on integrating comprehensive sex education into early childhood curricula, offering practical insights for policymakers and educators. Future research should explore the scalability of these approaches and their long-term impact on children’s safety and well-being.